(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The oral route is widely preferred for drug administration due to its simplicity, patient adherence, and formulation flexibility. However, this method faces challenges such as limited gastric residence time (GRT) for drugs absorbed in specific regions of the gastrointestinal tract (GIT) and for sustained drug delivery systems. Various strategies have been proposed to prolong the gastric retention of delivery systems in the upper GIT to overcome these limitations. Gastroretentive dosage forms (GRDFs) aim to achieve site-specific drug release in the upper GIT, thereby extending GRT. They enhance the bioavailability of drugs with narrow therapeutic windows and enable continuous, prolonged drug release, thereby increasing dosing intervals. This article aims to provide an overview of several gastroretentive methods developed to date. It discusses key factors influencing gastric retention to address the physiological challenges associated with achieving prolonged drug release in the stomach. Furthermore, the review evaluates criteria for gastroretentive drug delivery systems, summarizing various technologies including magnetic systems, high-density (sinking), floating, bio- or mucoadhesive, expandable, unfoldable, ultra-porous hydrogel, and other emerging approaches. This comprehensive study offers insights into the current landscape of gastroretentive drug delivery technologies, highlighting their potential in enhancing drug efficacy and patient outcomes.